Asymmetrical 3x1 Disk Patch Array with Rugby Ball Slot Microstrip Antenna for LoRa IoT B-OSA (Bidirectional Outdoor Sectoral Area) System - Bramantyo, Hutama Arif; Mujahidin, Irfan; Kitagawa, Akio; Apriantoro, Roni; Rochmatika, Rizkha Ajeng; Waluyo, Catur Budi (Politeknik Negeri Semarang, 2025)
Using minimal transmission power, Long-Range Wide Area Networks (LoRaWAN) enable the transmission of data via radio connections from sensors, which may be remote or challenging to reach, to gateways and servers linked to mobile networks for data processing, exchange, or relay, so generating numerous applications for object monitoring and tracking. Nonetheless, owing to its attributes of low data rates for low-power communications, information transmission utilizing LoRa technology is inadequate for rapid real-time data monitoring. Moreover, the narrow bandwidth of LoRa modulation techniques will yield minimal accuracy in localization efforts, as it cannot effectively address multipath issues. This paper proposes a multi-standard 3X1 Antenna Array and a LoRa end device that accurately measures locations using 3X1 technology and transmits this location data to the gateway and Internet of Things Network via LoRa. Measurement outcomes in both indoor and outdoor environments indicate that Antenna Array 3X1 achieves localization accuracy at the sub-meter level, specifically between 10 and 33 cm. Furthermore, Antenna Array 3X1 demonstrates ranges of 124 m in Line-of-Sight (LOS) scenarios and 55 m in Non-Line-of-Sight (NLOS) scenarios, respectively.